Falcipains as malarial drug targets - Kanzi, Aquillah Mumo (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Malaria is an infectious disease caused by parasites of the Plasmodium genus with mortality rates of more than a million annually, hence a major global public health concern. Plasmodium falciparum (P. falciparum) accounts for over 90% of malaria incidence. Increased resistance to antimalarial drugs by the Plasmodium parasite, coupled with the lack of an effective malaria vaccine necessitates the urgent need for new research avenues to develop novel and more potent antimalarial drugs. This study focused on falcipains, a group of P. falciparum cysteine proteases that belong to the clan CA and papain family C1, that have emerged as potential drug targets due to their involvement in a range of crucial functions in the P. falciparum life cycle. Recently, falcipain-2 has been validated as a drug target but little is known of its Plasmodium orthologs. Currently, there are several falcipain inhibitors that have been identified, most of which are peptide based but none has proceeded to drug development due to associated poor pharmacological profiles and susceptibility to degradation by host cysteine proteases. Non-peptides inhibitors have been shown to be more stable in vivo but limited information exists. In vivo studies on falcipain-2 and falcipain-3 inhibitors have also been complicated by varying outcomes, thus a good understanding of the structural variations of falcipain Plasmodium orthologs at the active site could go a long way to ease in vivo results interpretation and effective inhibitor design. In this study, we use bioinformatics approaches to perform comparative sequence and structural analysis and molecular docking to characterize protein-inhibitor interactions of falcipain homologs at the active site. Known FP-2 and FP-3 small molecule nonpeptide inhibitors were used to identify residue variations and their effect on inhibitor binding. This was done with the aim of screening a collection of selected non-peptide compounds of South African natural origin to identify possible new inhibitor leads. Natural compounds with high binding affinities across all Plasmodium orthologs were identified. These compounds were then used to search the ZINC database for similar compounds which could have better binding affinities across all selected falcipain homologs. Compounds with high binding affinities across all Plasmodium orthologs were found.
Keywords: Malaria; Malaria -- Chemotherapy; Plasmodium falciparum; Antimalarials -- Development; Cysteine proteinases; Cysteine proteinases -- Inhibitors; Papain; Drug development; Bioinformatics